Die Logik der europaïschen Agrarpolitik: Politische Macht oder ok̈onomische Gesetzmas̈sigkeiten? - Christian H.C.A. Henning; Carsten Struve; Martina Brockmeier (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
– This paper derives an applied general political economy model incorporating a model of political decision-making into a computable general economic equilibrium model. Political decision-making among a set of legislators is modeled via a mean voter decision rule derived from a modified non-cooperative legislative bargaining game of a BARON-FEREJOHN type. Legislators' preferences are endogenously derived from political support maximization, where policies translate into legislators' support according to a political transformation surface. Each surface reflects specific economic framework conditions of legislators' constituency. The model allows a simultaneous analysis of political and economic factors determining policy outcome. In regard to the Health Check proposal of the Commission the model is applied to simulate future Common Agricultural Policy (CAP) under various political and economic scenarios. Main results are: (i) MTR-reform will not be stable in the future. In particular, EU-enlargement and technical progress imply further reforms in 2013 corresponding to further liberalization of CAP and a further shift towards the second pillar, i.e. from market & price to structural policies. (ii) These general trends would be attenuated by increased world market prices, while additional WTO restriction would amplify these trends. (iii) Compared to economic and international policy factors, constitutional reforms, e.g. a higher participation of the European Parliament in CAP decision-making, have only moderate impact on future CAP, while changed financial rules would significantly reverse policy trends, i.e. reallocating budget from the second to the first pillar.
Keywords: 330; EU-Agrarpolitik; Agrarreform; Politische Entscheidung; Allgemeines Gleichgewicht; Verhandlungstheorie; EU-Staaten